Sister Bear : A Norse Tale - Yolen, Jane; Graves, Linda Dockey (Tarrytown, NY : Marshall Cavendish Children, 2011)
Halva is traveling with her trained bear to visit the King of Denmark when they stop for the night at a cottage where, they learn, a pack of trolls is about to make its annual Christmas Eve visit, causing trouble and making a big mess. Includes author's note about the story's origins.
Keywords: Folklore -- Juvenile literature. -- Norway; Folklore -- Norway